Secretor and Salivary ABO Blood Group Antigen Status Predict Rotavirus Vaccine Take in Infants. (18th January 2017) - Kazi, Abdul Momin; Cortese, Margaret M.; Yu, Ying; Lopman, Benjamin; Morrow, Ardythe L.; Fleming, Jessica A.; McNeal, Monica M.; Steele, A. Duncan; Parashar, Umesh D.; Zaidi, Anita K. M.; Ali, Asad
Summary: Histo-blood group antigens (HBGAs) expressed on enterocytes are proposed receptors for rotaviruses and measurable in saliva. Among Pakistani infants in a G1P[8] rotavirus vaccine trial, anti–rotavirus immunoglobulin A seroconversion rates after 3 vaccine doses differed significantly by HBGA phenotype. Abstract: Histo-blood group antigens (HBGAs) expressed on enterocytes are proposed receptors for rotaviruses and can be measured in saliva. Among 181 Pakistani infants in a G1P[8] rotavirus vaccine trial who were seronegative at baseline, anti–rotavirus immunoglobulin A seroconversion rates after 3 vaccine doses differed significantly by salivary HBGA phenotype, with the lowest rate (19%) among infants who were nonsecretors (ie, who did not express the carbohydrate synthesized by FUT2), an intermediate rate (30%) among secretors with non–blood group O, and the highest rate (51%) among secretors with O blood group. Differences in HBGA expression may be responsible for some of the discrepancy in the level of protection detected for the current rotavirus vaccines in low-income versus high-income settings.